Influence of adhesion between coating and substrate on the performance of coated HSS twist drills - Viana,R. (2009)
This work analyses the performance of the TiN/TiCN, TiAlN, TiN/TiAlN and TiN/TiAlN/WCC coatings on HSS M2 drills used in the drilling of the aluminium-silicon alloy ISO 3522 AlSi8Cu3Fe, correlating the life of the tools to the coating adhesion characterization experiments. Coating adhesion was characterized using Rockwell C indentation tests and scratch tests with progressive load. The performance of the coatings in the life experiments was the following, in decreasing order: TiN/TiCN, TiAlN, TiN/TiAlN/WCC and TiN/TiAlN. In the adhesion characterization experiments with TiN/TiCN there were no cracks or delamination of the coatings, which justifies its best performance in the life experiments.